Pemanfaatan Media Pembelajaran Berbasis Digital dalam Pembelajaran Menulis Puisi di SMP Negeri 2 Woja - Taufik, Taufik; Ismail, Ismail; Imansyah, M. Nur; Kasmita, Mayang Putri (LPPM Institut Pendidikan Nusantara Global, 2024)
Research has been conducted entitled the use of digital-based learning media in learning to write poetry at SMP Negeri 2 Woja, Dompu Regency. The main objective of this research is to carry out an in-depth analysis of the use of learning media that utilizes the use of technology in the process of learning to write poetry. This research uses a descriptive qualitative approach with the data collection techniques used are observation and writing performance. Meanwhile, the data analysis technique used in qualitative analysis has four stages, namely data collection, data reduction, data presentation and the final step is drawing conclusions and verification. The research results show that the use of learning media, especially technology-based learning media such as digital learning media, has proven effective in improving learning outcomes, especially in learning to write poetry. Digital learning media allows educators to present material in a more interesting and interactive way, motivating students to be more active in the learning process. Various learning media, such as Quizziz, PowerPoint, poetry anthologies, YouTube channels, and Instagram social media, can be used for various purposes in learning to write poetry, from understanding basic concepts to producing poetry and publishing it.